Computational elucidation of phylogenetic, structural and functional characteristics of Pseudomonas Lipases. (June 2018) - Pramanik, Krishnendu; Saren, Sunayana; Mitra, Soumik; Ghosh, Pallab Kumar; Maiti, Tushar Kanti
Graphical abstract: Highlights: A total of 84 lipase sequences of Pseudomonas aeruginosa were retrieved from NCBI. A detailed phylogenetic study was done based on lipases and cDNA of P. aeruginosa . Physicochemical characterization of all selected protein sequences was performed. Secondary structure of selected representative protein analyzed by various tools. 3D structure was assessed, validated from authentic servers and functions revealed. Abstract: Lipase (triacylglycerol acylhydrolase, EC 3.1.1.3) catalyzes tri-, di-, and monoacyl glycerol of fat into glycerol and fatty acids. It has important roles in the digestion of lipids in living organisms and industrially as laundry detergents along with proteases. The microbial lipases are more stable, active and economically feasible compared to plant and animal sources. Hence, much attention was given to the maximum production of the enzyme from the microbial sources. The phylogenetic analysis revealed that the amino acid sequence of lipase protein and their corresponding cDNA of Pseudomonas aeruginosa clustered with Pseudomonas stutzeri among different species of Pseudomonas, while P. aeruginosa PA1 clustered with P. aeruginosa SJTD-1 among different strains of P. aeruginosa . The lipase of P. aeruginosa PA1 was a monomeric, acidic and thermostable protein having a molecular weight ranging in between 32.72 to 34.89 kDa. The protein was abundant with random coils and alpha helices in its secondary structure. The tertiary model showed 96.310 score as an overall quality factor. Hence, this in silico study gives some useful information about the lipase protein without performing crystal structure assessment by X-ray Crystallography or NMR study in wet lab experiments which could be helpful for isolation and characterization of the enzyme in vitro .